(untitled) (Scientific journal of the Fergana State University, 2024)
This article explores the crucial role of diplomacy in Genghis Khan’s state-building efforts and territorial conquests. Drawing on the concepts of constructivism and political realism, the article examines how Genghis Khan’s diplomatic strategies were used to establish a centralized state in large parts of Eurasia. From a constructivist perspective, diplomacy refers to the creation of shared identities and norms among different tribes and peoples. On the other hand, from the perspective of political realism, diplomacy is interpreted as a pragmatic tool used by Genghis Khan to maximize his power and interests in order to lead conquests and build a state. In addition, the article talks about the system created by Genghis Khan and the territories he conquered.